The Effect of Anemia Education with Animated Videos on Adherence to Blood Added Tablet Consumption and Hemoglobin Levels of Young Women at SMPN 17 Samarinda - Febry Dwistika, Wulan; Dwi Utami, Kurniati; Anshory, Jamil (Politeknik Siber Cerdika Internasional, 2024)
Adolescent girls are at high risk of anemia. The results of the 2021 health screening are known that 46.15% of adolescent girls are at risk of anemia at SMPN 17 Samarinda. Lack of knowledge and awareness about anemia is a major challenge in handling this condition. This study aims to determine the effect of anemia education with animated videos on adherence to the consumption of blood-added tablets and hemoglobin levels of adolescent girls at SMPN 17 Samarinda. Quantitative research using quasi-experimental design with pretest-posttest approach with control group design. The number of samples was 36 people by purposive sampling divided into 2 groups, each 18 respondents in the experimental group with animated videos and controls with leaflets. The study was conducted from May to July 2023 at SMPN 17 Samarinda. Data collection in this study used MMAS-8 questionnaire and hemoglobin level examination. Data analysis using Wilcoxon and Mann-Whitney tests with significance levels ?=0.05. There was a significant difference in adherence to the consumption of blood-added tablets (p = 0.000) and hemoglobin levels (p = 0.000) in the experimental group with animated videos. In the control group with leaflets there was an increase in consumption adherence (p = 0.000), but there was no significant difference in hemoglobin levels (p = 0.112). There was a significant mean difference in adherence to the consumption of blood-added tablets (p = 0.002) and hemoglobin levels (p = 0.001) between the experimental group and the control group. Further research may be conducted by taking into account the consumption of foods containing iron using food consumption survey assessments so as to produce accurate data.